ANALISIS USAHA DAN STRATEGI PENGEMBANGAN AGROINDUSTRI DODOL NENAS DI KOTA DUMAI - Yulia Yulia; Novia Dewi; Roza Yulida (Indonesian Journal of Agricultural Economics, 2019)
Pineapple is the most widely cultivated commodity in Dumai City. The problem faced is the simultaneous harvest which caused the price of pineapple to drop drastically. To overcome this by making pineapple in order to get added value. The development of the current consumption pattern of the community makes the opportunity and threat to the development of pineapple dodol agroindustry in Dumai City. This study aims to analyze the development of pineapple dodol agroindustry in Dumai City as well as to know the amount of profit, efficiency and added value. One effort to know the right strategy for the development of pineapple dodol agroindustry is SWOT analysis. In the SWOT analysis, there are internal environmental analyzes that are Strength and Weakness and external environment analysis that is Opportunity and Threats. SWOT analysis shows that pineapple dodol agroindustry of Dumai City in quadrant I is a favorable situation. Agroindustry has the opportunity and power so that it can take advantage of existing opportunities. The strategy adopted under these conditions is to support an aggressive growth policy.The results showed the average production of pineapple dodol agroindustry of Dumai City amounted to 60.67 kg per month with a profit of Rp.2.003,847,86 per month. Efficiency of business to get value RCR> 1 is 1.78 which means that this agroindustry profitable if passed. While the added value of each kilogram of pineapple is Rp. 29,579.45. SWOT analysis shows that pineapple dodol agroindustry of Dumai City in quadrant I is a favorable situation. Agroindustry has the opportunity and power so that it can take advantage of existing opportunities. The strategy adopted under these conditions is to support an aggressive growth policy.